2015
DOI: 10.1590/1519-6984.24914
|View full text |Cite
|
Sign up to set email alerts
|

A bloom of cyanobacteria (Cylindrospermopsis raciborskii) in UHE Carlos Botelho (Lobo/Broa) reservoir: a consequence of global change?

Abstract: The UHE Carlos Botelho (Lobo/Broa reservoir) was selected in 1971 for a program of ecological research, and in the last 44 years continuous sampling and studies, characterized very well this artificial ecosystem and its watershed (Tundisi and Matsumura Tundisi, 2013). The mechanisms of functioning of the reservoir were well known and the maintenance of good water quality (low conductivity -average (10-20uSxcm -1 ; periodic turbulence with re-oxygenation of the whole water column, and high saturation of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 6 publications
1
23
0
5
Order By: Relevance
“…As extensively shown, CYN production is highly strain-dependent but geographically extends throughout the globe, encompassing Australia, New Zealand, Antarctica, Asia, South and North America, and Europe [3,81]. A number of its potential producers, such as R. raciborskii and Chrysosporum ovalisporum, are capable of forming blooms at different locations and under favorable conditions, such as eutrophication and increased water temperature [82,83]. As shown, CYN reveals a wide range of cytotoxic activities in vitro and in vivo [84] and was suggested as a causative factor of human poisoning on Palm Island, Australia in 1978 [17]; and, along with MCs, in fatal cases of patients undergoing treatment in a dialysis center in Caruaru, Brazil in 1996 [85].…”
Section: Cylindrospermopsin (Cyn)mentioning
confidence: 99%
“…As extensively shown, CYN production is highly strain-dependent but geographically extends throughout the globe, encompassing Australia, New Zealand, Antarctica, Asia, South and North America, and Europe [3,81]. A number of its potential producers, such as R. raciborskii and Chrysosporum ovalisporum, are capable of forming blooms at different locations and under favorable conditions, such as eutrophication and increased water temperature [82,83]. As shown, CYN reveals a wide range of cytotoxic activities in vitro and in vivo [84] and was suggested as a causative factor of human poisoning on Palm Island, Australia in 1978 [17]; and, along with MCs, in fatal cases of patients undergoing treatment in a dialysis center in Caruaru, Brazil in 1996 [85].…”
Section: Cylindrospermopsin (Cyn)mentioning
confidence: 99%
“…Limnology reports pointed about the damage on its aquatic biodiversity from biotic and abiotic sources (e.g. Pereira et al, 2008;Tundisi & Matsumura-Tundisi, 2014;Rodrigues-Filho et al, 2015;Tundisi et al, 2015). Rodrigues-Filho et al (2015) reported the multiple land uses influence the water bodies and their quality.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diversity of phytoplankton species, there are many optimum temperature ranges for growth (Seip and Reynolds, 1995), thus elevated temperatures may not change the size of the community, but rather species composition (Moss et al, 2003Van de Bund et al, 2004. Other studies, however, have found associations between increased temperature and frequency of cyanobacterial bloom phenomena (Reynolds, 2006;Jeppesen et al, 2009;Tundisi et al, 2015;Mowe et al, 2015b) and increased gross primary production (Yvon-Durocher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%